Profile of urban vs rural drivers detected drink driving via Roadside Breath Testing (RBT) in Queensland, Australia, between 2000 and 2011. (May 2017) - Armstrong, Kerry Ann; Watling, Hanna; Watson, Angela; Davey, Jeremy
Highlights: Rural–urban comparison of drink driving rates and characteristics of drivers explored. Results show that drink driving is more frequent in rural areas. Rural drink drivers are more likely to be male and reoffenders. Circumstances leading to drink driving in rural areas are different to urban areas. Abstract: Problem: In Australia, as in many other countries, a disproportionate number of drink driving crashes occur on rural roads. Aims and method: The study used Queensland Police Random Breath Testing (RBT) data from 2000–2011 to (a) comparing drink driving rates and RBT efficacy in areas of increasing remoteness (b) compare drink driver factors and the circumstances of apprehensions in rural and urban areas. Results: Generally, rural areas had a higher detection rate per RBT intercepts and a greater number of apprehensions per licensed drivers than the state average. Main effects showed that rural drivers were more likely to be male and to be a reoffender but less likely to be apprehended between midnight and 5.59 am and after visiting a licensed venue. Urban drivers were more likely to be aged 17–49 years and to be apprehended with a BAC < 0.15%. Conclusion: Differences in RBT effectiveness and drink driving factors and circumstances exist between rural and urban areas. Practical application: The greater number of drink drivers in rural areas signal a need for targeted interventions in these areas. To increase the effectiveness of such interventions, further research should examine the mechanisms responsible for these observed differences between rural and urban drink driver.